Variations and errors in the performance of excluded jejunal loops - Bogliaccini, Gustavo; Praderi, Raúl; Navarro, Teodoro (Cirugía del Uruguay, 1983)
Sone errors in the perfomance of excluded jejunal loops re preented. Difference between of being awre of the eror or not and jts onequences for the patient re pointed out. A brief historical revision of differents jejunal loops is done.